(untitled) (International Seven Journal of Health Research, 2023)
Introduction: Within the scope of the physiotherapist’s work in the health unit, there is also a need to assess the perception of the care provided by this professional, since assessing the quality of the service provided, the relationship between patient and professional and the physical structure for providing this service is indispensable for the good functioning of the unit. Objective: The purpose of this study is to analyze the perception of patients who are seen in the physiotherapy sector at the health unit in the municipality of Mucurici-ES. Methodology: This is a descriptive exploratory quantitative survey carried out with 24 patients, of both sexes, seen in the Physiotherapy sector in the town of Mucurici-ES. Results: In general, although 100% of all evaluations had positive responses regarding the perception of the physiotherapist’s care at the Mucurici health unit, it is worth noting, that it is also necessary to pay attention to the reason that there are studies that prove a tendency, on the part of patients from less favored social classes and lower education levels, to positively evaluate the services that are offered. Conclusion: In general, the perception of the patients treated at this health unit achieved good results, showing that the service is relevant and necessary, as well as being provided with quality, efficiency and an adequate structure for patients, according to their perception.